Inteligensi Pelajaran Fiqih Materi Hukum Perkawinan: Studi Penerapan Metode Quantum Learning - Yayuk Sri Wahyuni (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2017)
Intelligence education is used to determine the extent of learning achievement that can be achieved by individual, for adjustment in schools majors, and treatment to the educational subject. One of entrance examination for admission or continuing education and entry in workplace are through intelligence test. In problem solving, whether sooner or later, one of influence factor is the individualâ's intelligence. This research used class action study which consist of a series of four activities performed in a recurring cycle; (a) planning, (b) implementation, (c) observation, and (d) reflection. The result of this study are; there is an increase in Fiqh intelligence on the discussion of marriage law through the implementation of quantum learning in XI IPS 3 class of Madrasah Aliyah Negeri 1 Bojonegoro. The average value of intelligence of 78.33 raise into 81.75, so there is an increase in intelligence value of 3.42.